2015
DOI: 10.3390/admsci5040213
|View full text |Cite
|
Sign up to set email alerts
|

Local Management of National Cluster Policies: Comparative Case Studies of Japanese, German, and French Biotechnology Clusters

Abstract: Cluster policies have attracted increasing attention worldwide, but only a few studies have focused on their management by local cluster organizations. We investigate the relationship between national cluster policies and their management by local cluster organizations from a comparative perspective. For this purpose, we provide a detailed comparison of national cluster policies in Japan, Germany, and France as well as six prominent biotechnology clusters in these countries. Information on the focal clusters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…See Nishimura and Okamuro (2011) for Japan, Eickelpasch and Fritsch (2005) and Engel et al (2013) for Germany, and Fontagné et al (2013) and Martin, Mayer, and Mayneris (2011) for France. Okamuro and Nishimura (2011) provide a comparative study of recent national cluster policies in Japan, Germany, and France. 2.…”
Section: Notesmentioning
confidence: 99%
“…See Nishimura and Okamuro (2011) for Japan, Eickelpasch and Fritsch (2005) and Engel et al (2013) for Germany, and Fontagné et al (2013) and Martin, Mayer, and Mayneris (2011) for France. Okamuro and Nishimura (2011) provide a comparative study of recent national cluster policies in Japan, Germany, and France. 2.…”
Section: Notesmentioning
confidence: 99%
“…On the other hand, the Asian countries use the model led more by a government with a focus on specific industries. Okamuro and Nishimura (2015) have provided a comparison of national cluster policies in Europe and Asia. Based on their findings, cluster policy in Asian countries can be regarded as typical low-incentive policy accompanying the top-down selection of targeted clusters with a full funding scheme.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…The biotechnology industry is experiencing remarkable development today. Studies in many countries revealed the growth is mainly concentrated in cluster locations [24]. The industry is proved to be sustained by the linkage existence of five essential elements within ecosystems, which are academic research, experienced biotechnology entrepreneurs, funding sources, technically skilled workforce, and laboratory space and specialized facilities ( [24], [30]).…”
Section: B Biotechnology Start-ups and Its Challengesmentioning
confidence: 99%